The Unity of Form and Content: The Philosophical Patterns of the Great Commentary to the Book of Changes - Pischedda, Flaminia (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2022)
This paper focusses on the Xici 繫辭 ([Commentary to the] Appended Sentences), also called Dazhuan 大傳 (Great Commentary), which is included in the commentarial section attached to the Zhouyi 周易 (Zhou Changes), or Yijing 易經 (Classic of Changes), a pre-imperial Chinese divination text. I provide a formal analysis of the text, exploring its argumentative and philosophical patterns : without sidestepping the composite and multi-layered nature of this test, my analysis, conducted both on a micro and macro-level, highlights how the textual structure fundamentally reflects its content. The analysis will also show how structural and lexical elements make the Xici a kind of argument-based text as the philosophical argumentations are exhausted within the text itself.